Evaluation of the dentin changes in teeth subjected to endodontic treatment and photodynamic therapy - Mariane Floriano Lopes Santos LACERDA; Carolina Oliveira de LIMA; Gabriel Pinheiro LACERDA; Celso Neiva CAMPOS
Abstract Introduction Antimicrobial photodynamic therapy (PDT) is an efficient adjuvant technique to promote disinfection of the root canal system. Therefore, it is important to investigate changes to dentin morphology and permeability induced by the use of diode laser on the root dentin. Objective The purpose of this study was to investigate morphological changes and the percentage of apical leakage after the use of laser. Material and method Forty single-rooted teeth were instrumented using rotary system and irrigated. Teeth were randomly divided in two groups: G1 - not exposed to PDT (control), and G2 - pretreated with toluidine blue photosensitizer and irradiated with AsGaAl laser diode. Ten teeth in each group were evaluated by SEM for morphological changes. The other ten teeth were filled and stained with Rhodamine B to evaluate the apical leakage. Result The results showed significant difference between G1 and G2 (p <0.001 - chi-square), with greater presence of debris in G1 and higher incidence of open dentinal tubules in G2. Erosions and cracks were observed in both groups, with no statistically significant difference (p> 0.001). The apical leakage was significantly higher in G2 than in G1 (p <0.001 - Student's t-test). Conclusion It was concluded that the use of low-level laser reduced the smear layer and opened the dentinal tubules. Use of laser increased the permeability of the apical dentin.